Predicting PTSD and complex PTSD from interpersonal violence in Japanese school-based extracurricular sports activities: using the International Trauma Questionnaire (ITQ) - Toyoda, Hayato; Ishikawa, Katsuhiko; Omi, Yasuhiro (Frontiers in Psychology, 2024)
Interpersonal violence by coaches in sports is a severe international, ethical, and social concern. This study examined the applicability of the International Trauma Questionnaire (ITQ) and determined whether interpersonal violence victimization and related risk factors predicted post-traumatic stress disorder (PTSD) and complex PTSD (CPTSD) in extracurricular sports activities in Japan. We found that a high frequency of psychological and physical violence victimization experiences and selfidentified LGB (lesbian, gay, or bisexual) were associated with PTSD and CPTSD diagnosability. Meanwhile, being a woman and away from parents for school life was associated with PTSD diagnosability. This study is significant because it is the first quantitative study to examine CPTSD for interpersonal violence in sports and contributes to the consideration of psychological concerns in sports coaching through the negative mental health experiences of athletes exposed to violence and discrimination in the unique context of extracurricular sports activities in Japan. Additionally, clinical intervention and psychological support for victims of violence in sports have not yet been 2 established, and this study's findings about safe sports are applicable to practical situations related to sports psychology.